PELESTARIAN WARISAN BUDAYA MASYARAKAT TIONGHOA-JAMBI DAN KONFLIKNYA DALAM NOVEL MEMPELAI NAGA KARYA MEILIANA K.TANSRI: PENDEKATAN STRUKTURAL LÉVI STRAUSS - Die Bhakti Wardoyo Putro; Widowati Widowati (Universitas Sarjanawiyata Tamansiswa, 2014)
The purpose of this research was to describe (1) the structure of the novel Mempelai Naga according to Lévi Strauss, (2) conflict, (3) preservation of cultural heritage, (4) the values that can be applied as subject matter of Indonesian at high school. This research is qualitative and descriptive. The results of the study are (1) a novel structure according to Lévi Strauss has relationships, opposition, and transformation, (2) conflicts of conflict between man and man, man and nature, man and God, man and conscience and, (3) preservation of heritage Chinese culture-Jambi done by Naga who chose his bride and a number of elements relevant to the community, and (4) the value of which can be applied to learning Indonesian language and literature in high school are the value of cultural, moral, educational, religious, and social.